Building Harmony of Music Course Customer Loyalty in Jakarta: The Critical Role of Customer Value, Trust, Satisfaction, and Customer Engagement - Hernando Hernando; Liem Bambang Sugiyanto (PT. Publikasiku Academic Solution, 2024)
The music education industry in Indonesia, especially in Jakarta, is growing rapidly as people's interest in music increases. However, the industry faces challenges in retaining customers and increasing their loyalty. This study aims to identify the factors that affect Customer Loyalty of music course customers in Jakarta, focusing on the influence of customer value, trust, and customer satisfaction on Customer Loyalty, as well as the role of customer engagement as a mediation variable. This study uses a quantitative method with a survey approach. The sample consisted of 95 respondents who were consumers of music courses in Jakarta over 18 years old and had used music course services for at least three months. Data was collected through questionnaires and analyzed using Partial Least Squares (PLS) with SmartPLS software version 3.0. The results of this study are expected to provide insight for music course managers in developing effective marketing strategies to increase customer loyalty. By understanding the factors that affect Customer Loyalty, managers can increase customer value, build trust, and increase customer satisfaction, which will ultimately increase customer engagement and customer loyalty.